The Estimation of Quality-Adjusted Rates of Return in Stamp Auctions - Taylor, William M. (Journal of Finance, 1983)
The stamp auction market exemplifies markets in which a dominant feature is the quality variation in the traded assets. The observed price changes are a mixture of the “true” price change and the quality variation. This paper applies the time series signal extraction method to obtain estimates of quality-adjusted rates of return and quality-adjusted price indexes for stamp auction price series. The method is applicable to other areas in which there is quality variation or in which values are observed with error. Some features of stamps as an investment are also examined.